Perovskite Solar Cells: Sputtered Indium‐Zinc Oxide for Buffer Layer Free Semitransparent Perovskite Photovoltaic Devices in Perovskite/Silicon 4T‐Tandem Solar Cells (Adv. Mater. Interfaces 6/2021). Issue 6 (23rd March 2021) - Ying, Zhiqin; Zhu, Yudong; Feng, Xiyuan; Xiu, Jingwei; Zhang, Rui; Ma, Xuhang; Deng, Yunsheng; Pan, Hui; He, Zhubing
Abstract : Semitransparent solar cells can bring us a green, smart, and comfortable life powered by sun and compatible to our living buildings. In article number 2001604, Hui Pan, Zhubing He, and co‐workers develop high performance semitransparent perovskite solar cells in multidisciplinary applications, such as tandem solar cells, building integrated photovoltaics, smart window and etc.